STUDI LITERATUR TENTANG METODE PEMBELAJARAN KOOPERATIF TIPE TGT ( TEAM GAMES TOURNAMEN) UNTUK MENGEMBANGKAN KETERAMPILAN SOSIAL ANAK TAMAN KANAK-KANAK - Wiwik Anita; Siti Maisaroh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the effectiveness of the cooperative learning method Team Games Tournament(TGT) in developing social skills among kindergarten children through a literature review of national and international studies published within the last five years (2021–2025). The research employed a literature review approach by examining 25 relevant articles from reputable journals. The findings indicate that TGT consistently enhances various aspects of children’s social skills, including cooperation, communication, sharing, rule compliance, and prosocial behaviors. The structure of TGT—which integrates game-based activities, teamwork, and simple tournaments—provides meaningful social interaction experiences and increases children’s learning motivation. Moreover, the role of teachers as facilitators in managing group dynamics and instructional media becomes a key contributor to the successful implementation of TGT in early childhood education settings. Overall, this study confirms that TGT is an effective, enjoyable, and flexible approach for fostering social skill development in young children.